2013
DOI: 10.1111/jsm.12126
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functioning in Women with Mild and Severe Symptoms of Charcot-Marie-Tooth Disease

Abstract: Introduction Charcot-Marie-Tooth (CMT) disease is one of the most frequently inherited neurological disorders, and while it is known that individuals suffering from this condition have low quality of life, little is known about their sexual function and satisfaction. Aim To describe the functioning on different domains of sexuality in a relatively large sample of women with CMT, provide comparisons between mildly and severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…A total of 131 records were initially identified though database searching. Among them, nine [11,12,14,[16][17][18][19][20][21] were assessed for eligibility and five were included in the qualitative analysis [11,12,17,19,21]. The flow chart of the study is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 131 records were initially identified though database searching. Among them, nine [11,12,14,[16][17][18][19][20][21] were assessed for eligibility and five were included in the qualitative analysis [11,12,17,19,21]. The flow chart of the study is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, despite the lack of literature data investigating sexuality in CMT patients, this review provides evidence for the occurrence of LUTS, erectile and ejaculation disorders in men affected by this syndrome. However, many studies used questionnaires to evaluate the presence of urogenital dysfunction [16,17], resulting in contradictory data. Therefore, the presence of ED and anejaculation needs to be investigated more in depth and through more objective methods, such as penile Doppler evaluation, basal and post-orgasm prostate vesicular ultrasound examination, and penile biothesiometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of urogenital and sexual dysfunction has been already shown in women with CMT. 5 6 Lower urinary tract dysfunction (LUTS), 7 neurogenic bladder, ED, and sexual dysfunctions have been reported in male patients with CMT, 6 7 8 but the prevalence of such disturbances in patients with CMT is unknown. Unfortunately, the literature lacks of studies describing ejaculatory disorders in these patients.…”
mentioning
confidence: 99%
“…Unfortunately, the literature lacks of studies describing ejaculatory disorders in these patients. Furthermore, it should be kept in mind that the major of studies used questionnaires to evaluate the presence of urogenital dysfunction, 6 7 resulting in contradictory data. The presence of ED and anejaculation needs to be investigated through more objective methods, such as penile Doppler evaluation, basal and postorgasm prostate vesicular ultrasound examination, and penile biothesiometry.…”
mentioning
confidence: 99%